The Introduction of Basic Fibroblast Growth Factor Promotes Quadriceps Muscle Regeneration after Damage in Mice - Atefeh Mir; M. Amin tabatabaiefar; Seyedeh Sedigheh Baakhlagh; Hoora Jalali Tehrani; Mahdi Zamani (Journal of Sciences, Islamic Republic of Iran)
Tissue regeneration is the process of renewal and growth of damaging tissue. It is sometimes done by induction of an external biological factor(s) such as the Basic fibroblast growth factor (bFGF) which carries messages through its cellular receptor to induce biological processes such as cell growth, cell migration, cell survival, and cell differentiation. Due to the great importance of bFGF on cellular regeneration, in this study, we have concentrated on the effect of this factor on the regeneration of damaged muscle. In addition, the tumorigenic effect of this factor during this regenerative process was studied. In this study, we employed inbred mice. The cultured male mouse muscle cells were transplanted into the damaged muscle tissues of HLA_matched female mice. After about one month, selected samples from the transplanted regions of the female mice were analyzed. DNA was extracted from the samples and Sex determination was done to track the potential cell growth and repair by the introduced male cells in the presence and absence of bFGF. The tumorigenic effect of bFGF on this process was also assessed. We found that bFGF had a remarkable effect on damaged muscle regeneration compared to cells without injection of this factor, and more concentration of bFGF was determined to be more effective in muscle regeneration. However, no association was observed with tumorigenesis regarding bFGF injection. According to our findings, bFGF was effective in the regeneration of the injury site and confirmed the results of previous studies. However, no association was found with tumorigenesis.